2017
DOI: 10.1111/jac.12226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term elevation of air temperature on sucrose metabolism in cotton leaves at different positions

Abstract: Global warming could possibly increase the air temperature by 1.8–4.0°C in the coming decade. To forecast the effects of long‐term elevation of air temperature on sucrose synthesis in cotton leaves at different positions, field experiments with the treatments of ambient temperature (control) and elevated temperature (2–3°C) across cotton's boll forming stage were conducted in 2011 and 2012. Results showed that sucrose content in the fourth main‐stem leaves from the terminal (FMLT) during 10–17 days after treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Carbohydrates play a critical role in developing endosperm during the early seed development stage of cotton (Hu et al 2017). Carbohydrates are the basis for the synthesis of oil and protein in cottonseed, contributing to the carbon skeletons needed in developing seeds (Braun et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrates play a critical role in developing endosperm during the early seed development stage of cotton (Hu et al 2017). Carbohydrates are the basis for the synthesis of oil and protein in cottonseed, contributing to the carbon skeletons needed in developing seeds (Braun et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although the extent and the severity of drought stress can limit cotton growth, it is also important to note that cotton plants can continue to grow once returned to well‐watered conditions. Consequently, it has been shown that the conditions under which each boll set and developed across different fruiting branches were different (Davidonis, Johnson, Landivar, & Fernandez, ; Hu et al, ). Whether cotton plants were under waterlogging stress, shading or nutrient stress, it is clear that different fruiting branches playing an important role in the formation of cotton fibre quality traits (Jie et al, ; Lv et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has proven that ET from 32 C upwards could block photosynthesis (Reddy et al, 1995). Hu et al (2017) also…”
Section: Discussionmentioning
confidence: 90%
“…SuSy activity and its related genes were upregulated, which accelerated the sucrose decomposition. The increased activity of cy‐FBPase and SPS (regulated by GhSPSs ) promoted sucrose synthesis and ultimately increased sucrose content (Chen et al, 2017; Hu et al, 2017). In addition, increased SPS activity inhibited starch accumulation in leaves (Hashida et al, 2016), which may indirectly increase “Carbon” allocation to sucrose.…”
Section: Discussionmentioning
confidence: 99%